Antidiabetic Potential of Senna siamea: α-Glucosidase Inhibition, Postprandial Blood Glucose Reduction, Toxicity Evaluation, and Molecular Docking - Suthinee Sangkanu; Armad Heemman; Sathianpong Phoopha; Thanet Pitakbut; Wandee Udomuksorn; Sukanya Dej-adisai (Scientifica)
Senna siamea (Lam.) H.S. Irwin & Barneby is used in Thai cuisine. This plant is also used in traditional treatments, including diabetes. Therefore, this study aims to examine the antihyperglycemic effects of S. siamea heartwood extract. The ethanolic extract of S. siamea heartwood exhibited activity against α-glucosidase enzyme with IC50 values of 54.4 μg/mL. Moreover, S. siamea extract (250–1000 mg/kg BW) was tested using normal rats with and without sucrose of 3 g/kg BW administration. The results showed that all extract concentrations significantly reduced fasting blood glucose compared with the control. In addition, results also agreed with the amount of sucrose in the small intestine of rats. In the acute toxicity study, a single dose of the S. siamea extract at 2000 mg/kg BW caused no mortality, and hematological and biochemical parameters also revealed no toxic effects of the extract on rats. The subchronic toxicity study, administration of the extract for 90 days, at 250 mg/kg BW, caused no significant changes in the hematological and biochemical parameters of rats in the treated groups compared with the control group. However, histopathology of the liver and kidney indicated an inflammatory response at 500 and 1000 mg/kg BW of the extract, correlating to hematological and biochemical findings. Finally, molecular docking was conducted to evaluate theoretical interactions between three main stilbenes previously found in S. siamea extract and mammalian α-glucosidases (Wistar rat and human). The simulation supported the in vivo study and suggested the potential for human glucosidase inhibition. Therefore, S. siamea could be a promising candidate against α-glucosidase. This study offers encouraging information on the potential of natural compounds from S. siamea to act as α-glucosidase inhibitors for diabetes treatment through drug development or dietary supplement for hyperglycemia individuals.